Potensi Pelepah Daun Pisang Kepok Sebagai Hand Sanitizer Alami - Fadhilah, Nur Lailatul; , Triastuti Rahayu, M.Si (2017)
Banana leaf plants contain chemical compounds such as saponins, tannins and flavonoids. Such compounds to function in the field of medicine. While the sap of banana bark contains saponins, antakruinon and quinones which is antibacterial, so it can be used as a natural hand sanitizer. The purpose of this study is to determine the potential of banana leaf as a natural hand sanitizer as well as determine the effectiveness in decreasing the number of bacterial colonies with different lag time after use. This study was an experimental study using a completely randomized design (CRD) 1 factor is the type of hand sanitizer, bacterial inoculation was conducted using a replica of the media Nutrient Agar (NA) which are further incubated for 24 hours. After incubation, bacterial colonies are counted and statistically tested using Post Hoc Test by test Sceffe. The result Hand sanitizer leaf midrib with a lag time of 5 minutes can reduce the number of bacterial colonies more than the hand sanitizer A. Hand sanitizer A with a lag time of 3 minutes has the most excellent antibacterial activity. So it concluded that kepok banana leaf extract can lower the number of colonies of bacteria are constantly in a longer period of time than hand sanitizer A.